Qualitative perspectives of Medicaid-insured patients on ambulatory care at an academic medical center: challenges and opportunities - Mariah B. Blegen; Jessica Faiz; Daniel Gonzalez; Vanessa Nuñez; Nina Harawa; Medell Briggs-Malonson; Gery Ryan; Katherine L. Kahn (BMC, 2024)
Abstract Background Ambulatory access to academic medical centers (AMCs) for patients insured with Medi-Cal (i.e., Medicaid in California) is understudied, particularly among the 85% of beneficiaries enrolled in managed care plans. As more AMCs develop partnerships with these plans, data on patient experiences of access to care and quality are needed to guide patient-centered improvements in care delivery. Methods The authors conducted semi-structured, qualitative interviews with Medi-Cal-insured patients with initial visits at a large, urban AMC during 2022. Participant recruitment was informed by a database of ambulatory Medi-Cal encounters. The interview guide covered Medi-Cal enrollment, scheduling, and visit experience. Interviews were transcribed and inductively coded, then organized into themes across four domains: access, affordability, patient-provider interactions, and continuity. Results Twenty participant interviews were completed (55% female, 85% English speaking, 80% self-identified minority or "other" race, and 30% Hispanic or Latino) with primary and/or specialty care visits. Within the access domain, participants reported delays with Medi-Cal enrollment and access to specialist care or testing, though appointment scheduling was reported to be easy. Affordability concerns included out-of-pocket medical and parking costs, and missed income when patients or families skipped work to facilitate care coordination. Participants considered clear, bilateral communication with providers fundamental to positive patient-provider interactions. Some participants perceived discrimination by providers based on their insurance status. Participants valued continuity, but experienced frustration arising from frequent and unexpected health plan changes that disrupted care with their established AMC providers. Conclusions The missions of AMCs typically focus on clinical care, education, research, and equity. However, reports from Medi-Cal insured patients receiving care at AMCs highlight their stress and confusion related to inconsistent provider access, uncompensated costs, variability in perceptions of quality, and fragmented care. Recommendations based upon patient-reported concerns suggest opportunities for AMC health system-level improvements that are compatible with AMC missions.